STRATEGI KOMUNIKASI ANTARPRIBADI DALAM NEGOSIASI BISNIS PADA UMKM di Jakarta - Argarini, Fitri (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
Kata Kunci: Strategi komunikasi, komunikasi antarpribadi, negosiasi bisnis, UMKM, Jakarta. Abstract - This study aims to analyze interpersonal communication strategies applied by Micro, Small, and Medium Enterprises (MSMEs) in business negotiations in Jakarta. Interpersonal communication plays an essential role in building effective working relationships, establishing trust, and achieving mutually beneficial agreements. This research employs a descriptive qualitative method using a case study approach. Data were collected through in-depth interviews, observations, and documentation involving MSME actors from various sectors, such as culinary, fashion, and services. The results indicate that MSME actors use several communication strategies, including persuasive strategies to influence business partners, empathetic strategies to build emotional closeness, and adaptive strategies adjusted to the context and characteristics of negotiation partners. Factors such as honesty, openness, listening skills, and understanding of local culture strengthen communication effectiveness during negotiations. The study concludes that successful business negotiations among MSMEs are not only determined by bargaining skills but also by interpersonal communication competence, which helps create long-term and mutually beneficial business relationships.